The Effectiveness of Compilation of Islamic Law in Resolving Inheritance Disputes at the Religious Courts of Panyabungan and Padang Sidempuan City - Muhammad Fadlan Is; Defel Fakhyeldi; Azizatur Rahmah (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2022)
Debate and rejection of some of the Compilation of Islamic Law (KHI) materials regarding inheritance always occur among Indonesian Muslims. Not all provisions in KHI can be accepted by society, especially by Muslims in Panyabungan and Padangsidimpuan City. Several "pasal" must be criticized because they contradict the qat'i texts and have abolished the common fiqh laws in society. In this study, two problem formulations will be answered: How is the implementation of inheritance dispute resolution in the Religious Courts? Second, how effective is the Compilation of Islamic Law in ​​inheritance disputes in the Religious Courts? The type of research used in this study is empirical juridical research using a field research approach. The two locations were chosen because there were differences in settlement of inheritance disputes in their respective Religious Courts. The theory used is Lawrence M. Friedman's legal system. They state that the effectiveness of law enforcement depends on three elements: legal structure, legal substance, and legal culture. Inheritance disputes that enter the average are the determination of heirs. From a structural perspective, judges are influential because they use the KHI Legal Justice approach.